The Social Networks of Korean Female Adult Learners in a Middle School - Keunho Kim; Hyewon Park; Hyunah Yang (Adult Education Research Conference, 2018)
This study investigates the social networks of Korean female adult learners in middle school through social network analysis and examines the development of these networks by interviewing the main actors involved.
Keywords: social network; female adult learner; social network analysis